SUNNAH-SUNNAH FITHRAH - Anshori, Muhammad (UIN Sunan Kalijaga Yogyakarta, 2014)
This article discusses about the five of sunna of fithrah namely khitan (to circumcise), to shave the hair of penis (istihdÄd), shave the hair of armpit (natf al-ibt), cutting the nails (taqlÄ«m al-azÄfÄ«r) and cutting the moustache (qas al-syÄrib) in six hadith books (al-kutub al-sittah). These five of sunna of fithrah did by Muslim society although they didâ€™nt know the evidence or hadith. This article also explained about the chain of transmitter (sanad/isnad) and content of the hadith (matn) so we know who and where the hadith of sunna of fithrah. Besides that, this article tried to explains briefly about thats depend on the modern sciences. The modern research of sciences found that if we always do this five sunna of fithrah we will free from the disease, especially cancer, etc.